Increased CO2 selectivity of asphalt-derived porous carbon through introduction of water into pore space. Issue 12 (December 2017) - Jalilov, Almaz; Li, Yilun; Kittrell, Carter; Tour, James
Abstract The development of inexpensive porous solid sorbents, such as porous carbons, that can selectively capture carbon dioxide (CO2 ) from natural gas wells is essential to reduce emission of CO2 to the atmosphere. However, at higher pressures, the selectivity for CO2 over that for methane (CH4 ) remains poor. Here we show that H2 O can be imbibed within asphalt-derived porous carbon, with a surface area of 4, 200 m2 g−1,  to generate a hydrated powder material. While maintaining a high CO2 uptake capacity of 48 mmol g−1 (211 wt%), the molar selectivity for CO2 over CH4 increases to >200:1 and the H2 O remains within the pores on repeated cycling. To mimic realistic natural gas wells, we used a 90% CH4 and 10% CO2 gas mixture and showed selective CO2 separation at 20 bar. Furthermore, in situ vibrational spectroscopy reveals the formation of an ordered matrix within the pores consisting of gas hydrates. CO2 is often found alongside CH4 in natural gas wells; therefore, separation of the gases is an important industrial process. Jalilov et al. demonstrate that the adsorption selectivity for CO2 over CH4 can be significantly enhanced through introduction of water into the pores of a high-surface-area carbon.